IMPROVING TYPOGRAPHY MATERIAL COMPREHENSION THROUGH COLLABORATIVE LEARNING METHODS USING COGNITIVE DIAGNOSTIC ASSESSMENT IN JUNIOR HIGH SCHOOL (SMP) STUDENTS - Anggara, Anggara Putra Kurniawan; Iriaji (Eduarts: Jurnal Pendidikan Seni, 2025)
This study was motivated by the low level of understanding of typography theory among seventh-grade students at SMP Negeri 1 Singosari. The purpose of this study is to improve their comprehension of typography art material through the implementation of the collaborative learning method combined with cognitive diagnostic assessment. The research approach used is descriptive qualitative, employing a Classroom Action Research (CAR) design consisting of two cycles, each with stages of planning, implementation, observation, and reflection. The data sources for this study were 33 students from class VII-D, with data types including results from cognitive diagnostic assessment tests, student analysis outcomes, student creativity results, and records from each cycle. Data analysis results showed an increase in the average cognitive diagnostic assessment scores from 84.2 in the pre-action stage to 90 for skills scores and 82.6 for work analysis scores in Cycle I. These scores further improved to 93.3 for skills and 84.5 for analysis in Cycle II. The conclusion of this study is that the implementation of the collaborative learning method through cognitive diagnostic assessment can significantly enhance students' understanding of typography.